2013
DOI: 10.1590/0102-311x00077512
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of physical inactivity and associated factors among adolescents from public schools in Uruguaiana, Rio Grande do Sul State, Brazil

Abstract: This study aimed to identify the prevalence of physical inactivity and associated factors in adolescents, using a cross-sectional design with a sample of 1,455 adolescents (741 females

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
27
2
16

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 36 publications
(43 reference statements)
6
27
2
16
Order By: Relevance
“…In the adjusted analysis study Bergmann et al (2013), noted that older adolescents tend to be inactive; these results corroborate with the study of Ruiz et al, (2011) the average level of physical activity was lower among older European adolescents (2.4% per age group increase). Specifically in Spain, it was identified that adolescents aging between 17-18 years are more inactive than adolescents with 11-12 years old (Ramos et al, 2012).…”
supporting
confidence: 84%
“…In the adjusted analysis study Bergmann et al (2013), noted that older adolescents tend to be inactive; these results corroborate with the study of Ruiz et al, (2011) the average level of physical activity was lower among older European adolescents (2.4% per age group increase). Specifically in Spain, it was identified that adolescents aging between 17-18 years are more inactive than adolescents with 11-12 years old (Ramos et al, 2012).…”
supporting
confidence: 84%
“…Many studies have also revealed high prevalence of physical inactivity among adolescents. This represents a problem about the future since this profile of inactivity tends to be maintained over the years 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Porém, adolescentes do sexo feminino e com idades mais avançadas apresentaram mais chance de não atenderem às recomendações para ApC e F/R, enquanto indivíduos do sexo masculino e com menor idade para Flex. Em um estudo realizado com adolescentes desta população 22 , foi encontrado que as meninas e os indivíduos com idades mais avançadas apresentam NAF mais baixos que os meninos e do que os indivíduos de menor idade. Isto pode ajudar a explicar os resultados encontrados para as associações entre sexo, idade e a baixa ApC e a baixa F/R.…”
Section: Discussionunclassified
“…A EF escolar parece ser um importante espaço para o desenvolvimento de conhecimentos práticos e teóricos que podem contribuir para um estilo de vida mais ativo e, consequentemente, para melhores níveis de ApFRS. Adolescentes que participam e gostam das aulas de EF escolar tendem a ser mais ativos 22 e a apresentar melhores níveis de ApC 11 . Estes achados são reforçados considerando que o período de férias escolar parece ser negativo para os níveis de ApFRS de adolescentes, principalmente em relação à ApC 26 .…”
Section: Discussionunclassified